Advantages of expanded hemodialysis (HDx) over standard hemodialysis - N.G. Aleksieieva (Український Журнал Нефрології та Діалізу, 2019)
Chronic kidney disease leads to the accumulation of a wide range of uremic toxins. Negative effects of uremic toxins are most likely due to the combined effects of many uremic solutes, including small molecules, middle molecules, and soluble protein-linked substances. Large and medium-sized molecules are directly associated with chronic inflammation and adverse effects, including major cardiovascular risks and consequently poor prognosis.